Stress Testing the Enterprise Sector's Bank Debt - a Micro Approach - Eivind Bernhardsen; Bjørne Dyre H. Syversten (Norges Bank, 2008)
This paper describes Norges Bank's micro stress testing framework for assessing the Norwegian banking sector's losses on loans to the non-financial enterprise sector. Using projected macro variables and a stock-flow approach, annual financial statements of every firm in Norway are projected five years ahead. The loan loss potential is then assessed using a credit scoring model. We present a backtest of projections taking the history of macro variables as given. Our results are fairly good using a relatively simple set-up, and we conclude that stock-flow projections of financial statements can be useful for stress testing banks' loan portfolios.
hdl:11250/2507963
Keywords: G21; G32; G33; M49; 330